Chronic ethanol intake leads to structural and molecular alterations in the rat endometrium - Martinez, Marcelo; Milton, Flora A.; Pinheiro, Patricia Fernanda F. [UNESP]; Almeida-Francia, Camila C.D. [UNESP]; Cagnon-Quitete, Valeria H.A.; Tirapelli, Luiz F.; Padovani, Carlos Roberto [UNESP]; Chuffa, Luiz Gustavo A. [UNESP]; Martinez, Francisco Eduardo [UNESP] (Elsevier, 2016)
We described the effects of low- and high-dose ethanol intake on the structure and apoptosis signaling of the uterine endometrium of UChA and UChB rats (animals with voluntary ethanol consumption). Thirty adult female rats, 90 days old, were divided into three groups (n = 10/group): UChA rats fed with 10% (v/v) ethanol ad libitum (free choice for water or ethanol) drinking < 1.9 g/kg/day; UChB rats fed with 10% (v/v) ethanol ad libitum (free choice for water or ethanol) drinking from 2 to 5 g/kg/day; control rats without ethanol (only water). After 120 days of treatment, rats displaying estrus were euthanized. Uterine epithelial cells of the UCh rats showed dilated cisterns of the rough endoplasmic reticulum, presence of lipid droplets, altered nuclear chromatin, and disrupted mitochondria. The UCh rats exhibited intense atrophied epithelial cells with smaller areas and perimeters of cytoplasm and nuclei. The endometrium of UChA rats showed higher levels of caspase-3 while Xiap and Bcl2 varied from moderate to weak. Both UChA and UChB rats exhibited a stronger immunoreaction to Ki-67 and IGFR-1 on epithelial and stromal cells. Chronic ethanol intake leads to structural and molecular alterations in the uterine endometrium of UCh rats, regardless of low- or high-dose consumption, promoting reproductive disorders.
Keywords: Apoptosis; Epithelium; Ethanol; TEM; UCh rat; Uterus